The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/foods12050938
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Evidence of the Multifunctional Features of Lactiplantibacillus pentosus LPG1, a Natural Fermenting Agent Isolated from Table Olive Biofilms

Abstract: In recent years, there has been a growing interest in obtaining probiotic bacteria from plant origins. This is the case of Lactiplantibacillus pentosus LPG1, a lactic acid bacterial strain isolated from table olive biofilms with proven multifunctional features. In this work, we have sequenced and closed the complete genome of L. pentosus LPG1 using both Illumina and PacBio technologies. Our intention is to carry out a comprehensive bioinformatics analysis and whole-genome annotation for a further complete eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 123 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…Whole-genome sequencing (WGS) of Lp. pentosus LPG1 isolated from table olive biofilms confirmed the multifunctional features of this strain, as various genes involved in acid stress resistance, bile salt tolerance, carbohydrate metabolism and adhesion were found [57]. Pan-genome analysis of the LPG1 strain revealed that IG8, IG9, IG11, and IG12 were the more closely related strains, all of them isolated from table olive biofilms.…”
Section: Genomicsmentioning
confidence: 55%
“…Whole-genome sequencing (WGS) of Lp. pentosus LPG1 isolated from table olive biofilms confirmed the multifunctional features of this strain, as various genes involved in acid stress resistance, bile salt tolerance, carbohydrate metabolism and adhesion were found [57]. Pan-genome analysis of the LPG1 strain revealed that IG8, IG9, IG11, and IG12 were the more closely related strains, all of them isolated from table olive biofilms.…”
Section: Genomicsmentioning
confidence: 55%
“…The LPG1 annotated genome was used for mapping. The genome of LPG1 has a length of 3,700,533 bp distributed among one chromosome and two plasmids, which contain a total of 3,345 protein-coding genes and 89 non-coding sequences (73 tRNA and 16 rRNA genes), with a G + C content of 46.34% ( López-García et al, 2023a ). Regarding mapping quality, the mean coverage of the samples was more than 300%, and the mean mapping quality of the samples reached a value of 58, with a mean insert size of 154 bp.…”
Section: Resultsmentioning
confidence: 99%
“…LPG1 has shown remarkable technological features such as esterase and phytase activity, production of lactic acid, bacteriocin production, etc., ( Benítez-Cabello et al, 2019 ). A recent genomic analysis of the LPG1 strain has revealed various genes involved in adhesion, biofilm formation, bacteriocin production, degradation of carbohydrates, and metabolism of phenolic compounds, among these important technological features ( López-García et al, 2023a ). This microorganism has also shown important potential probiotic features, proving to be an anti-inflammatory agent, reduce cholesterol levels, inhibit foodborne pathogens, and adhere to Caco−2 cells ( Benítez-Cabello et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the CARD database search yielded 195 genes with a concordance range of 21.9-75.8% and coverage of 9.5-100% for matched regions. The loose hits included genes associated with resistance mechanisms such as antibiotic target alteration (66), antibiotic target protection (13), antibiotic efflux (106), antibiotic inactivation (7), and antibiotic target replacement (3). No drug resistance genes were annotated when the identity was ≥90% and coverage was ≥60%.…”
Section: Phenotypic Antibiotic Resistance and Safety-related Gene Ass...mentioning
confidence: 99%